BARRIERS TO COMPETITIVE FRINGE EXPANSION AS A SEED OF MARKET POWER - Gerasymenko, Anzhelika (Economic Annals, 2012)
Starting from the behavioural approach to economic competition, this paper enlarges the traditional view of economics on the essence of potential competition by including not only the potency of competition from new but also the potency of competition from existing firms of the competitive fringe and from distant substitutes because of their ability to be actualised upon changes in market conjuncture. The author specifies three types of barriers to potential competition: barriers to entry, barriers to switching demand, and barriers to competitive fringe expansion. This paper is devoted to the analysis of the latter, answering the question of their influence on the market power of incumbent firms. The theoretical and empirical analysis in the paper explains the important role of establishment and exploitation of barriers to competitive fringe expansion in maintaining the market power of a dominant firm and the maximization of its economic rent.